2019
DOI: 10.1021/acsphotonics.9b00685
|View full text |Cite
|
Sign up to set email alerts
|

Single Fluorescent Peptide Nanodots

Abstract: Fluorescent peptide nanodots (PNDs) are bioorganic nanoparticles self-assembled from peptide biomolecules of different origin and complexity. These recently discovered nanodots of biological origin are highly promising for biomedical imaging applications due to their biocompatibility, bright and tunable fluorescence over the entire visible range and photostability. Here we apply single-particle microscopy methods to study the photophysical properties of individual PNDs. We show that the fluorescence spectrum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The amyloidogenic structures under study exhibit exclusive broadband, fully overlapped FL and OA spectra (Figure 1 and 3), which are created by the electronic structure of noncovalent hydrogen bonds responsible for visible FL in amyloid structures. [ 9–12,14–17 ] FL and OA effects are detected along the entire visible spectrum in the 400–650 nm range. This effect provides the observation of any FL visible color, blue, green, yellow, red, and more.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amyloidogenic structures under study exhibit exclusive broadband, fully overlapped FL and OA spectra (Figure 1 and 3), which are created by the electronic structure of noncovalent hydrogen bonds responsible for visible FL in amyloid structures. [ 9–12,14–17 ] FL and OA effects are detected along the entire visible spectrum in the 400–650 nm range. This effect provides the observation of any FL visible color, blue, green, yellow, red, and more.…”
Section: Resultsmentioning
confidence: 99%
“…This intrinsic, structure‐sensitive bio‐effect has been observed in a variety of β‐sheet disease‐related human peptide amyloid fibrils, [ 10,11 ] native silk fibrils, [ 12 ] synthetic vapor‐deposited diphenylalanine (FF)‐fibers, [ 13 ] bioinspired thermally refolded diaromatic and triaromatic and aliphatic peptide nanostructures, [ 9,14 ] and recently in peptide/protein nanodots. [ 15,16 ] Regardless of their composition and origin, they irradiate FL in a similar visible range within a wide spectral maximum in the blue region. Recently, a deep study of amyloid fibrils involving 13 different amyloid proteins showed that, in addition to its blue component, the amyloid FL signal also contains a red near‐infrared FL spectral component with wavelengths of 780–820 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the bioinspired materials, we observed similar fibrillary structures grown under the thermally induced transformation of the native helix-like state to the β-sheet one. These β-sheet amyloidogenic fibers deeply change original non-fluorescent optical properties and lead to the appearance in the β-sheet state of a new fold-sensitive effect of visible FL phenomenon in the region~400-700 nm [2,3,[89][90][91][92][93]. Figure 10 accumulates basic experimental data on the helix-like→β-sheet transition and FL phenomena in bioinspired materials.…”
Section: Visible Fl In Bioinspired Amyloidogenic B-sheet Structuresmentioning
confidence: 90%
“…All of them displayed visible FL effects, which were ascribed to electron delocalization caused by hydrogen bonds in the β-sheet structure, providing low energy electronic transitions. Later, this new and unusual visible FL was disclosed in two different large classes of amyloid [1,[85][86][87][88] and amyloidogenic [2,3,[89][90][91][92][93] peptide/protein structures as well as in a new generation of hybrid polymer/peptide thin films and fiber materials [94,95]. All of them were folded into a β-sheet secondary structure.…”
Section: Intrinsic Fluorescence In Amyloid Fibrilsmentioning
confidence: 96%